1977
DOI: 10.2134/agronj1977.00021962006900050026x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Greenhouse‐grown Cannabis sativa L. to Nitrogen, Phosphorus, and Potassium1

Abstract: Growers of illegal Cannabis sativa L. use various cultural practices to maximize crop production. The objective of this study was to evaluate the morphological and biochemical responses of greenhouse grown C. sativa to soil incorporated N, P, and K as they reflect the geographical origin of Cannabis derivatives. Fertilizers were blended with Ap horizon soil from a Gilpin silt loam before placement in 12‐cm pots. NH4NO3‐N was applied at 0, 25, and 125 ppm. Phosphorus and K from super‐phosphate and KCI, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 2 publications
2
40
0
Order By: Relevance
“…The results of all set of elements are listed in Table 3 together with the data obtained from literature where by comparison the Brazilian samples presented high Fe, Sr and Ba levels and low concentrations of Mo and Cu. 8,9 It can be observed that nutrient contents in samples from Region 1 (Mato Grosso do Sul) were high, mainly for Cu and Fe. Aluminium, Ga and Ba levels were also higher than those for the other groups (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of all set of elements are listed in Table 3 together with the data obtained from literature where by comparison the Brazilian samples presented high Fe, Sr and Ba levels and low concentrations of Mo and Cu. 8,9 It can be observed that nutrient contents in samples from Region 1 (Mato Grosso do Sul) were high, mainly for Cu and Fe. Aluminium, Ga and Ba levels were also higher than those for the other groups (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…38 In comparison to the literature data, Cu and Zn concentrations for these samples were similar to those obtained by Landi,14 although lower than those presented by Coffman and Gentner. 9 It is well known that Zn deficiency is the most generalized and critical in those regions and is probably related to the composition of the parent material. 38 The Mo value in Cannabis samples was also lower than those available in the literature, which may point out to a deficiency of this element in the soil.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations